1981
DOI: 10.1177/00220345810600090301
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stannous Fluoride Treatments on the Progression of Initial Lesions in Approximal Surfaces of Permanent Posterior Teeth

Abstract: Bite-wing radiographs were used to determine the effect of three forms of topical SnF2 therapy on the progression of initial lesions in the approximal surfaces of permanent posterior teeth. Radiographs were taken annually over a four-year period. The subjects were schoolchildren, aged 12-14 yr, living in a low fluoride area. The professional application of a 10% SnF2 solution for 30 s, semi-annually for two yr, had no discernible effect on the development of the initial lesions. However, the home use of a SnF2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1983
1983
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The increasing experimental evidence show ing the ability of fluoride to arrest or even repair enamel lesions has been supported to date by rel atively few clinical studies [Hollender and Koch, 1969;Hyde, 1973;Powell et al, 1981;Axelsson et al, 1987],…”
Section: Discussionmentioning
confidence: 99%
“…The increasing experimental evidence show ing the ability of fluoride to arrest or even repair enamel lesions has been supported to date by rel atively few clinical studies [Hollender and Koch, 1969;Hyde, 1973;Powell et al, 1981;Axelsson et al, 1987],…”
Section: Discussionmentioning
confidence: 99%
“…Having completed cavity design, the dentine should be conditioned ready for the application of the glass-ionomer cement using either polyacrylic acid (5)(6)(7)(8)(9)(10) seconds) or tannic acid (30 seconds). Flush the cavity thoroughly, dry it but do not dehydrate and place the glass-ionomer cement of choice.…”
Section: Composite Resin In Combination With Glass-ionomer Cementmentioning
confidence: 99%
“…There are few studies reported in the dental literature that have examined the problem of overlapping carefully, particularly in primary dentitions (23,24) while there are many clinical trials that make no mention of exclusions due to overlapping (8,12,25,26).…”
Section: Frequency Of Overlappingmentioning
confidence: 99%
“…In another study of adult dentitions HAUGEJORDEN (1) excluded 31-39% of surfaces as unreadable. Definitions of overlapping on radiographs and rules for exclusion vary greatly in previous caries epidemiological studies, studies of radiographic methodology and clinical trials (6)(7)(8)11,12,(23)(24)(25)(26)(27). Even though these studies give a contradictory picture of the importance of loss of data due to overlapping, it seems clear that overlapping surfaces is a common source of error that may often be compounded in longitudinal studies.…”
Section: Frequency Of Overlappingmentioning
confidence: 99%
See 1 more Smart Citation